-
Notifications
You must be signed in to change notification settings - Fork 2
/
Copy path2011fall_p2.tex
122 lines (113 loc) · 3.82 KB
/
2011fall_p2.tex
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%
%%%% Problem 1
%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%%
\problem{1}
\subsubsection{Question}
% Keywords
\index{Lagrangian!Pendulum from free horizontal support}
\index{mechanics!Pendulum from free horizontal support}
Mass $m₁$ moves freely along a fixed, long, horizontal rod. The position of
$m₁$ on the rod is $x$. A massless string of length $ℓ$ is attached to $m₁$
at the end and to mass $m₂$ at the other. Mass $m₂$ executes pendulum motion
in the vertical plane containing the rod.
\begin{enumerate}
\item
Find the Lagrangian of the system.
\item
Derive the equations of motion and the corresponding conservation laws.
\item
Assume that $x(0)=x₀$, $\dot x(0)=0$, $φ(0)=φ₀$ $(|φ₀| ≪ 1)$,
and $\dot φ(0)=0$. Find $x(t)$ and $φ(t)$ for $t > 0$.
\end{enumerate}
\subsubsection{Answer (1)}
For the sliding support mass $m₁$:
\begin{align*}
T₁ &= \frac{1}{2}m₁ \dot{x}² \\
V₁ &= 0
\end{align*}
For the pendulum mass $m₂$:
\begin{align*}
T₂ &= \frac{1}{2}m₂ \dot{y}² + \frac{1}{2}m₂(\dot x + \dot x₂)² \\
V₂ &= -m₂gy₂ \\
\intertext{Then using $x₂ = ℓ\sin φ$ and $y₂ = -ℓ\cos φ$,}
T₂ &= \frac{1}{2}m₂ \left( ℓ²\dot φ² + \dot x² + 2ℓ\dot φ\dot x \cos φ
\right) \\
V₂ &= -m₂ g y₂
\end{align*}
Putting the Lagrangian together equals the first line. Applying the small
angle approximation gives the second line where the kinetic energy term
involving $\cos φ$ can be simply expanded as $\cos φ ≈ 1$, but the potential
energy term must be expanded to second order so that $\cos φ ≈ 1 -
\frac{1}{2}φ²$.
\begin{align}
\boxed{
\sL = \frac{1}{2} (m₁ + m₂)\dot x² + \frac{1}{2} m₂ \left(
ℓ²\dot φ² + 2ℓ\dot φ\dot x\cos φ \right) + m₂gℓ\cos φ
}
\\
\boxed{
\sL ≈ \frac{1}{2} (m₁ + m₂)\dot x² + \frac{1}{2} m₂ \left(
ℓ²\dot φ² + 2ℓ\dot φ\dot x \right) + m₂gℓ - \frac{1}{2}m₂gℓφ²
}
\end{align}
\subsubsection{Answer (2)}
Constructing the Euler-Lagrange equations for $x$ and $\dot x$:
\begin{align*}
\frac{∂\sL}{∂x} &= 0 &
\frac{∂\sL}{∂\dot x} &= (m₁ + m₂)\dot x + m₂ℓ\dot φ
\\
{}&{}&
\frac{d}{dt}\left[ \frac{∂\sL}{∂\dot x} \right]
&= (m₁ + m₂)\ddot x + m₂ℓ\ddot φ
\end{align*}
\begin{align}
(m₁ + m₂)\ddot x + m₂ℓ\ddot φ = 0
\end{align}
and for $φ$ and $\dot φ$:
\begin{align*}
\frac{∂\sL}{∂φ} &= -m₂gℓφ &
\frac{∂\sL}{∂\dot φ} &= m₂ℓ²\dot φ + m₂ℓ\dot x
\\
{}&{}&
\frac{d}{dt}\left[ \frac{∂\sL}{∂\dot φ} \right]
&= m₂ℓ²\ddot φ + m₂ℓ\ddot x
\end{align*}
\begin{align}
-m₂gℓφ - m₂ℓ²\ddot φ + m₂ℓ\ddot x = 0
\end{align}
The equations of motion are:
\begin{align}
\boxed{
\ddot x + \frac{m₂}{m₁+m₂} ℓ \ddot φ = 0
} \\
\boxed{
\ddot φ + \frac{1}{ℓ}\ddot x + \frac{g}{ℓ}φ = 0
}
\end{align}
\subsubsection{Answer (3)}
Solve for $\ddot x$ and substitute into the other differential equation
\begin{align}
\ddot φ - \frac{1}{ℓ}\frac{m₂}{m₁+m₂} ℓ \ddot φ + \frac{g}{ℓ}φ &= 0\nonumber
\\
\frac{m₁}{m₁+m₂} \ddot φ + \frac{g}{ℓ}φ &= 0\nonumber
\\
\ddot φ + \frac{g}{ℓ}\frac{m₁+m₂}{m₁} φ &= 0
\end{align}
This is just the differential equation for a simple harmonic oscillator, so
considering the given boundary conditions,
\begin{align}
\boxed{
φ(t) = φ₀\cos(ωt)
\quad\quad\text{where } ω² = \frac{g}{ℓ}\frac{m₁+m₂}{m₁}
}
\end{align}
Then differentiating $φ(t)$ twice and substituting into the first equation,
\begin{align*}
\ddot x &= ℓφ₀ω²\frac{m₂}{m₁+m₂}\cos(ωt)
\end{align*}
Then integrating twice and applying the boundary conditions,
\begin{align}
\boxed{
x(t) = x₀ - \frac{g}{ω²}\frac{m₂}{m₁}\cos(ωt)
}
\end{align}